ANALISIS KUALITATIF ATAS POTENSI DAN HAMBATAN PEMUNGUTAN PAJAK PENGHASILAN CONTENT CREATOR FACEBOOK PROFESSIONAL DI KOTA KUPANG - Hortensia Ade Sonya; Cicilia A. Tungga; Aldarine Molidya (Journal of Innovation Research and Knowledge, 2026)
This research aims to analyze the potential and obstacles of Income Tax collection as well as the level of compliance of professional Facebook content creators in reporting and paying Income Tax (PPh) in Kupang City using a qualitative approach. The data sources in this study are primary and secondary data sources. Data were collected through in-depth interviews with content creators, tax consultants, and analysis of related documents. The data was then analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing/verification. The results of the study show that the potential for tax collection from content creators is quite high in line with the increase in the number of creators and the amount of income. However, the main obstacles faced are low tax awareness, the absence of a specific business classification (KLU) for content creators, and a lack of transparency in the tax deduction mechanism. The level of compliance among content creators in reporting and paying taxes also varies.